Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages MATERNAL MORTALITY IT will be remembered that our Conference of 1930 was called to consider the Interim Report of the Departmental Committee on Maternal Mortality. We restate at the beginning of this Report the resolution on which our Conference of 1930 ended :— This Conference declares its agreement with the recommendations of the Report which supports its previous demands for an effective national maternity service based on (i) an increase in the length and content of the training of medical students in obstetrics and on (ii) essential services to be provided as follows :— (a) The provision in every case of the services of a qualified midwife to act either as midwife or as maternity nurse. (b) The provision of a doctor to carry out ante-natal and post-natal examination in every case, and to attend during pregnancy, labour and the puerperium, as may prove necessary, all cases showing any abnormality. (c) The provision of a consultant, when desired by the doctor in attendance, during pregnancy, labour and puerperium. (d) The provision of hospital beds for such cases as need institutional care. (e) The provision of certain ancillary services (e.g. home helps, transport, sterilised equipment, laboratory facilities). The Conference recognises that some of the services now in operation have been due to voluntary effort. It urges the co-ordination of such voluntary effort with the work of Public Authorities in order to enlist the widest possible interest and support in solving this problem, and expresses its conviction that the Departmental Committee is right in its conclusion that full success in reducing maternal death and morbidity can only be obtained by the co-ordination and extension of the various services in a national maternity service. That resolution indicated the lines of our policy for the ensuing year. (3) 292/824/1/58